Peter & Ernesto. Sloths in the night - Annable, Graham (First Second, 2020)
"Peter and Ernesto love the jungle, but they know how dangerous it can be at night. From clumsy bats to crazed owls to rumors of a dragon, there are countless things that make the darkness perilous for sloths. That's why, one day, when their friend Bernard goes missing just as the sun is setting, Peter and Ernesto quickly gather their tribe to form a search party. However, while these sloths have some sense of the dangers that they'll face while looking for Bernard, there are surprises lurking in the shadows that will surpass their wildest imaginings!"--Provided by publisher.